Impact of Traumatic Disorder on Families of United Nation Soldiers Deployed on Peace Keeping Missions - Chi, Nevile (Journal of International Relations, 2023)
Purpose: The study sought to investigate the use of impact of traumatic disorder on families of United Nation soldiers deployed on peace keeping missions. Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings show that wives of military personnel on peacekeeping mission are beleaguered by a number of psychosocial problems among which are loneliness, fear that the husbands might lose their lives during the mission, children missing their fathers and lack of guidance and counseling on how coping could be achieved. Unique Contribution to Theory, Practice and Policy: The quantity of life theory was very instrumental in this study, future studies anchored on different context could benefit from the theory. The study recommended that, there is need to pay increased attention to military families affected by combat deployment to the current conflicts. Transitions such as those engendered by the deployment cycle offer prime opportunities to strengthen already present skills and introduce new strategies. Policy maker's needs to provide a framework for understanding and supporting military families affected by deployment, and adapt, a new implementation of family care being developed specifically for military families that empowers parents to be their children's best teachers.